Predictors of Mortality of Pediatric Patients with COVID-19 in Dr Moewardi General Hospital Surakarta - Aprilizia, Dwi Suryaning Ayu; Andarini, Ismiranti; Hafidh, Yulidar (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: COVID-19 has spread all over the world and became a global pandemic. In Indonesia, COVID-19 has officially defined the non-natural disaster of COVID-19 spread as national disaster in April 13th 2020. COVID-19 cases are predominant in adult population with higher severity particularly if accompanied with comorbidities resulting in a relatively high mortality rate. However, some recent studies showed that children are at a similar or higher risk to COVID-19 compared to adults. This study aims to evaluate the predictors of mortality in pediatric COVID-19 cases.Subjects and Method: This study used a cross-sectional design using data from medical records of pediatric patients with confirmed COVID-19 who were hospitalized in the isolation ward of Dr Moewardi General Hospital from March 2020 to August 2021. All variables with significant result in the bivariate analysis were analyzed using multivariate logistic regression. Data were analyzed using SPSS (IBM SPSS Statistics version 25) with significance of p value of < 0.05.Results: Results of this study showed that age 10-17 years (OR= 16.26; 95% CI= 1.47 to 179.56; p= 0.023), the use of oxygen mask (OR= 45.89; 95% CI = 5.39 to 390.58; p <0.001), and the use of continued oxygen therapy (OR= 181.48; 95% CI=11.25 to 2927.80; p <0.001) are predictors of mortality in pediatric patients with confirmed COVID-19.Conclusion: Age 10-17 years, use of oxygen mask and advanced oxygen therapy are predictors of mortality in pediatric patients with COVID-19 hospitalized in Dr Moewardi General Hospital Surakarta.Keywords: mortality, COVID-19, pediatric.Correspondence: